2020
DOI: 10.1186/s12884-020-03067-8
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to maternal retention in HIV care in Ghana: key differences during pregnancy and the postpartum period

Abstract: Background: Maternal retention in HIV care is lower for women in the postpartum period than during pregnancy, but the reasons are poorly understood. We examined key differences in barriers to retention in HIV care during and after pregnancy. Methods: We conducted semi-structured, in-depth interviews with 30 postpartum women living with HIV. Participants were recruited from two tertiary facilities implementing Option B+ for prevention of mother-to-child HIV transmission in Accra, Ghana. We collected data from m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…This is because the information was not readily available in the medical records retrieved. Ghana has an active HIV program with HAART as an integral component of the mother‐to‐child Transmission Prevention Program implemented among pregnant women 25 . However, some challenges hamper the proper intake of HAART among pregnant women, including reported adverse effects of antiretroviral drugs, lifestyle behaviors, and HIV stigma, among others 26…”
Section: Discussionmentioning
confidence: 99%
“…This is because the information was not readily available in the medical records retrieved. Ghana has an active HIV program with HAART as an integral component of the mother‐to‐child Transmission Prevention Program implemented among pregnant women 25 . However, some challenges hamper the proper intake of HAART among pregnant women, including reported adverse effects of antiretroviral drugs, lifestyle behaviors, and HIV stigma, among others 26…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicate that PLHIV commonly confronts various distress and unmet medical care needs 4 5. Moreover, the issue of HIV-related discrimination also acts as a barrier to PLHIV seeking medical and psychosocial support 6 7. Therefore, more medical care resources, especially those that can lower PLHIV’s psychological defences, are needed to improve PLHIV’s quality of life, thus promoting the achievement of the ‘95-95-95’ goal (95% of PLHIV know their HIV infection, 95% of PLHIV with HIV-positive diagnosis receive ART, 95% of PLHIV on ART achieve viral load suppression)8 and improving health-related quality of life for PLHIV at any stage 9…”
Section: Introductionmentioning
confidence: 99%
“…Sakyi et al … found that the increased tendency of postpartum mothers to be lost to HIV care was due to two factors: the experiences of poverty and HIV stigma [ 8 ]. This is confirmed by systematic reviews and meta-analyses of the many studies of pregnant and postpartum women living with HIV [ 9 ].…”
Section: Introductionmentioning
confidence: 99%